Xeno-miRNA in Maternal-Infant Immune Crosstalk: An Aid to Disease Alleviation - Stephen, Bjorn John; Pareek, Nidhi; Saeed, Mohd; Kausar, Mohd Adnan; Rahman, Safikur; Datta, Manali (Frontiers in Immunology, 2020)
Human milk is a complex liquid that contains multifaceted compounds which provide nutrition to infants and helps to develop their immune system. The presence of secretory immunoglobulins (IgA), leucocytes, lysozyme, lactoferrin, etc., in breast milk and their role in imparting passive immunity to infants as well as modulating development of an infant's immune system is well-established. Breast milk miRNAs (microRNAs) have been found to be differentially expressed in diverse tissues and biological processes during various molecular functions. Lactation is reported to assist mothers and their offspring to adapt to an ever-changing food supply. It has been observed that certain subtypes of miRNAs exist that are codified by non-human genomes but are still present in circulation. They have been termed as xeno-miRNA (XenomiRs). XenomiRs in humans have been found from various exogenous sources. Route of entry in human systems have been mainly dietary. The possibility of miRNAs taken up into mammalian circulation through diet, and thereby effecting gene expression, is a distinct possibility. This mechanism suggests an interesting possibility that dietary foods may modulate the immune strength of infants via highly specific post-transcriptional regulatory information present in mother's milk. This serves as a major breakthrough in understanding the fundamentals of nutrition and cross-organism communication. In this review, we elaborate and understand the complex crosstalk of XenomiRs present in mother's milk and their plausible role in modulating the infant immune system against infectious and inflammatory diseases.